The Epidemiology of Hepatitis in the Marche Region (Italy): A Notification System over a Decade (2012–2021) - Cosimo Damiano Giorgio Mangino; Corinna Fortunato; Love Chibuzor Ilochonwu; Andrea Mazzacchera; Davide Mengarelli detto Rinaldini; Giulia Mercante; Andrea Paladini; Fabio Filippetti (Medical Sciences Forum)
The World Health Organization has highlighted the substantial impact of viral hepatitis on individuals, healthcare systems, and economies worldwide. This study’s objective is to monitor disease notifications to assess their trends. Data from infectious disease notifications detected in the Marche Region (Italy) were analyzed and entered into the Nuovo Sistema Informativo Sanitario portal between 1 January 2012 and 31 December 2021. In this period, there were 399 confirmed reports, of which 47.9% were for hepatitis A, 26.8% were for hepatitis B, 7% were for hepatitis C, and 18.3% were for hepatitis E; 67.4% of the afflicted individuals were male, and the average age was 43.5 years old. The year with the highest peak was 2017, accounting for 18% of the reports, while the year with the lowest number was 2020, followed by 2021, accounting for 3.8% and 4.5%, respectively. Effective surveillance systems are key to combating the spread of hepatitis and reducing its impact, although they have been affected by the SARS-CoV-2 pandemic, with many cases remaining undetected.